A technique for fast application of heated solutions of different composition to cultured neurones - Dittert, I; Vlachová, V; Knotková, H; Vitásková, Z; Vyklicky, L; Kress, M; Reeh, P W (Journal of neuroscience methods, 1998)
A technique is described that allows the application of fast temperature changes (time constant approximately 300 ms) of solutions superfusing cultured neurones under whole-cell mode of membrane current recording. Its principle is in heating the common outlet of the manifold which consists of 12 tubes connected to barrels containing test solutions of different composition. The outlet is made from a glass capillary (25 mm length, 620/350 microns outer/inner diameter) coated on the outside wall with platinum for a length of 12 mm. The heating element, a platinum layer, is electrically connected to the probe fixed to the micromanipulator used for positioning the manifold. The solutions, driven by gravity, are applied by opening electronic valves controlled either manually or in programmed sequences. The DC current for heating is controlled either manually or by external voltage command. The advantage of the technique is that the same temperature pattern can be applied to 12 different solutions. The technique is used for classifying sensory neurones in culture with respect to their sensitivity to heat and algogens; however, it is applicable to any study of the effects of increased temperature on the activity of ion channels in cultured cells.
Keywords: cytologické techniky; lékové roztoky; buněčná membrána; neurony; kultivační média; Pharmaceutical Solutions; Cells, Cultured; Cell Membrane; Cytological Techniques; kultivované buňky; vysoká teplota; Hot Temperature; Culture Media; Neurons